(untitled) (Revista LIDER, 2021)
This paper analyzes the neo-extractivism that prevails in Chile as part of the establishment of the neoliberal economic model in the seventies of the 20th century, as well as the rol of the Chilean State as agent of the same and as producer of a market space in which converge various extractive activities, analyzing the contrast between this space and the sacred spaces of the Mapuche people, in the particular case of the mobilization in defense of the Sacred Space of the Ngen Kintuante in Pilmaikén River against various megaprojects, reflecting on the injustice around this situation and on the right to the sacred of the indigenous communities of the place, identifying the legal support to which they can appeal to access said space, as well as the challenges of the Chilean State regarding this fundamental right of the indigenous peoples that inhabit it.